Pleiotropic Phenotypes Associated With PKP2 Variants - Novelli, Valeria; Malkani, Kabir; Cerrone, Marina (Frontiers in Cardiovascular Medicine, 2018)
Plakophilin-2 (PKP2) is a component of the desmosome complex and known for its role in cell-cell adhesion. Recently, alterations in the Pkp2 gene have been associated with different inherited cardiac conditions including Arrythmogenic Cardiomyopathy (ACM or ARVC), Brugada syndrome (BrS), and idiopathic ventricular fibrillation to name the most relevant. However, the assessment of pathogenicity regarding the genetic variations associated with Pkp2 is still a challenging task: the gene has a high variability and the potential deleterious role of several of its variants has been disputed. Limitations in facilitating interpretation and annotations of these variants are seen in the lack of segregation data and clinical information in the control population of reference. In this review we will provide a summary of all the genetic information related to the Pkp2 gene, including variants associated to different phenotypes, ClinVar annotations and data from large control database. Our goal is to provide a literature review that could help clinicians and geneticists in interpreting the role of Pkp2 variants in the context of heritable sudden death syndromes. Limitations of current algorithms and data repositories will be discussed.